Lower Turonian (Upper Cretaceous) Watinoceras devonense Zone ammonite fauna in Colorado, USA - Kennedy, W; Cobban, W; Elder, W; Kirkland, J (1999)
The basal Turonian Watinoceras devonense Zone fauna from the Bridge Creek Member of the Greenhorn Limestone in southeastern Colorado is described and illustrated, including material from the Rock Canyon area near Pueblo, where the base of bed 86, which corresponds to the first appearance of W. devonense Wright and Kennedy, 1981, has been proposed as Global Boundary Stratotype Section and Point for the base of the Turonian stage. The fauna includes Watinoceras devonense devonense Wright and Kennedy, 1981, W. depressum Wright and Kennedy, 1981, W. praecursor Wright and Kennedy, 1981, Quitmaniceras reaseri Powell, 1963, Quitmaniceras sp. nov.?, Allocrioceras larvatum (Conrad, 1855), and Hamites cimarronensis (Kauffman and Powell, 1977). A remarkable aspect of the assemblage is the presence of three co-occurring species of Watinoceras that were originally described from Devon, England (Wright and Kennedy, 1981), so that the Watinoceras devonense Zone is a biostratigraphic unit that allows trans-Atlantic correlation of the base of the Turonian Stage.